A Real-life Picture of Medieval Healing: A Stylistic Study of Old English Medical Text Lacnunga - Zhang, Junqi (2023)
This thesis discusses the real-life situation of early medieval medical practice in England. It focuses on the remedies of Lacnunga, an Old English medical collection which has been suggested by scholars as a guide for real medical practice. By conducting a broad analysis on its remedies that are various in contents and styles, this thesis aims to answer the questions of the ways in which these remedies were used and transmitted. To do so, it employs a stylistic approach to examine the remedies in Lacnunga.